P8 TRANSVENOUS LEAD EXTRACTION AS LIFE–SAVING PROCEDURE IN SEPTIC SHOCK. (18th May 2022) - Dentico, A; Ferrieri, A; Epicoco, G; Troccoli, R; Carretta, F; D'Agostino, C; Carretta, D
Abstract: Introduction: With the increase of implant centers and the related procedures also increased the complications associated with the pacemakers and defibrillators implant. Transvenous lead extraction, saving procedure in presence of sepsis or septic shock, is the best therapy for leads' infections because medical treatment alone is not effective to eradicating the infection. Materials and Methods: In May 2021 was sent to our O.U. from the ER a 61–year–old patient for symptomatic Afib with rapid ventricular response. In 2014 the patient received an ICD implantation for obstructive hypertrophic cardiomyopathy, later found to be an amyloidosic infiltrative cardiomyopathy. The TEE reported EF 30%, thrombus filling left and right atrial appendage and vegetations all over the lead. Despite the patient was apyretic, laboratory tests showed neutrophilic leukocytosis and an increase in inflammation indices. The series of blood cultures were instead negative. However, for the occurrence of septic state, has been set up an antibiotic therapy and DOACs therapy on the advice of an infectious disease specialist. PET TAC confirmed an infection along leads. For a progressive clinical improvement, the patient started a cardiological rehabilitation cycle. Six days later, due to the onset of hyperpyressia and septic shock, the patient was intubated bacause of an acute respiratory failure and transferred urgently in intensive care. For the onset of MOF by sepsis on an endocarditic basis, has been indicated an extraction procedure. Results: After performing the extraction procedure, it was found an immediate improvement of both the clinical conditions and laboratory parameters. In fact the next day it was possible to proceed to the extubation. Laboratory tests showed a progressive normalization of inflammation and leukocytosis indices; TEE confirmed the absence of vegetations and thrombotic material in the atrial appendage. The patient, apyretic, was sent to cardiological rehabilitation to complete the antibiotic–therapy cycle and, subsequently, at home with Life Vest. After cardiological revaluation and in absence of sepsis signs, the patient was re–implanted with a contralateral ICD. Conclusions: In accordance with guidelines and literature, transvenous leads extraction constitutes, despite the potential risks associated with the procedure, the true resolutive therapy in device infections.